Familial Risk of Wolff-Parkinson-White Syndrome a Nationwide Family Study in Sweden - Ricci, Fabrizio; Pirouzifard, Mirnabi; Galanti, Kristian; Sundquist, Jan; Sundquist, Kristina; Sutton, Richard; Fedorowski, Artur ; 0000-0002-5352-6327; Zöller, Bengt ; 0000-0002-8250-5613 (Europace : European pacing, arrhythmias, and cardiac electrophysiology : journal of the working groups on cardiac pacing, arrhythmias, and cardiac cellular electrophysiology of the European Society of Cardiology, 2025)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a rare cardiac disorder that predispose to supraventricular arrhythmias. Prognosis is usually benign, yet there is an increased lifetime risk of sudden death. While typically sporadic, familial clustering has been reported. This study aimed to assess the risk of WPW, arrhythmias, and mortality among siblings of individuals with WPW. METHODS: This population-based sibling cohort included 5,338,434 individuals born in Sweden (1932-2018), with 3,172 WPW cases identified from the Swedish National Patient Registers. Familial risks among siblings were assessed using incidence rate ratios (IRRs) and adjusted subdistributional hazard ratios (SHRs). Sensitivity analyses excluded syndromic WPW and cases without electrophysiologic procedural confirmation. RESULTS: Although familial occurrence of WPW was exceedingly rare with only 14 of 3,172 cases (0.4%; ≈0.0003% of the total population), siblings of affected individuals showed a significantly higher rate of WPW diagnosis (0.121 vs. 0.032 per 1,000 person-years; IRR 3.83; 95%CI 2.27-6.46; p<0.001) translating to an almost fourfold higher adjusted risk (SHR 3.79; 95%CI 1.81-7.97; p<0.001). Risks of atrial fibrillation (SHR 1.19; 95%CI 1.05-1.35; p<0.01) and ventricular arrhythmias (SHR 1.84; 95%CI 1.45-2.35; p<0.001) were also higher, whereas all-cause mortality was comparable irrespective of sibling history (HR 1.01; 95% CI 0.92-1.11; p=0.88). CONCLUSIONS: WPW features familial aggregation and increased arrhythmic risk among siblings of affected individuals despite its extremely low absolute frequency in the general population. The evidence of a measurable hereditary component within an otherwise sporadic, non-syndromic condition points to a genetic contribution driven by complex inheritance patterns.
© The Author(s) 2025. Published by Oxford University Press on behalf of the European Society of Cardiology.